Future Dreams
Future Dreams is a swim coaching business started by the former New Zealand swimmer-turned triathlete Haydn Woolley. It was founded in early 1998 and is the most individualised swim-training system for triathletes that can be found on the Internet today. The primary focus of Future Dreams is the constant and varied stimulation of the body to improve swimming efficiency and planning fitness levels to coincide with important race dates.